Applications in osteochondral organoids for osteoarthritis research: from pathomimetic modeling to tissue engineering repair - Jiao, Yingguang; Lu, Shanyu; Zhang, Jianwei; Zhen, Junping (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoarthritis (OA) is a prevalent degenerative joint disorder characterized by complex tissue interactions, featuring cartilage degradation, synovitis, and aberrant subchondral bone remodeling. Current therapies often fail to halt disease progression and typically lack comprehensive strategies targeting OA pathogenesis. Osteochondral organoids have recently emerged as innovative 3D biological models for investigating OA mechanisms and developing personalized therapies. These models recapitulate dynamic cell-cell and cell-matrix interactions within the articular microenvironment. This review evaluates progress in applying osteochondral organoids to osteoarthritis, focusing on their fabrication strategies, applications, and key challenges. It emphasizes their role in osteoarthritis modeling, drug screening, and cartilage regeneration, while exploring future directions for their development. Despite these advances, clinical translation of osteochondral organoids faces significant challenges, including standardization, vascularization, and immunomodulation. Future integration with organ-on-chip platforms, multi-omics, and AI promises to create more precise OA research models. Such integration will bridge the gap between bench research and clinical practice.